(untitled) (Diametros, 2013)
This article considers the development of the idea of universal moral principles in the work of Thomas Aquinas and his predecessors in the thirteenth century. Like other medieval authors who sought to place the principles of moral practice on a foundation more secure than on the choices of the good person, as described by Aristotle, Thomas chooses to introduce a measure of ethical certitude through the concept of the innate habit of synderesis. This idea, introduced by Jerome in his commentary on Ezekiel, locates an inextinguishable spark of conscience in all humans. Thomas, influenced by Philip the Chancellor and Albert the Great, locates the principles of natural law in this innate habit of synderesis. By so doing he can claim that all human beings have the ability to recognize universally binding moral imperatives, regardless of their background and societal influences. Through this natural ability the human basis for moral action found in Aristotle’s Ethics yields to one based upon the eternal immutable laws of a divine being.